LIS1 and NDEL1 Regulate Axonal Trafficking of Mitochondria in Mature Neurons - Pandey, Jai P.; Shi, Liang; Brebion, Remi A.; Smith, Deanna S. (Frontiers in Molecular Neuroscience, 2022)
Defective mitochondrial dynamics in axons have been linked to both developmental and late-onset neurological disorders. Axonal trafficking is in large part governed by the microtubule motors kinesin-1 and cytoplasmic dynein 1 (dynein). Dynein is the primary retrograde transport motor in axons, and mutations in dynein and many of its regulators also cause neurological diseases. Depletion of LIS1, famous for linking dynein deregulation to lissencephaly (smooth brain), in adult mice leads to severe neurological phenotypes, demonstrating post-developmental roles. LIS1 stimulates retrograde transport of acidic organelles in cultured adult rat dorsal root ganglion (DRG) axons but findings on its role in mitochondrial trafficking have been inconsistent and have not been reported for adult axons. Here we report that there is an increased number of mitochondria in cross-sections of sciatic nerve axons from adult LIS1+/– mice. This is probably related to reduced dynein activity as axons from adult rat nerves exposed to the dynein inhibitor, ciliobrevin D also had increased numbers of mitochondria. Moreover, LIS1 overexpression (OE) in cultured adult rat DRG axons stimulated retrograde mitochondrial transport while LIS1 knockdown (KD) or expression of a LIS1 dynein-binding mutant (LIS1-K147A) inhibited retrograde transport, as did KD of dynein heavy chain (DHC). These findings are consistent with our report on acidic organelles. However, KD of NDEL1, a LIS1 and dynein binding protein, or expression of a LIS1 NDEL1-binding mutant (LIS1-R212A) also dramatically impacted retrograde mitochondrial transport, which was not the case for acidic organelles. Manipulations that disrupted retrograde mitochondrial transport also increased the average length of axonal mitochondria, suggesting a role for dynein in fusion or fission events. Our data point to cargo specificity in NDEL1 function and raise the possibility that defects in the LIS1/NDEL1 dynein regulatory pathway could contribute to mitochondrial diseases with axonal pathologies.